Business Strategy of Decorative Plants Cultivation in Sub-District of Bacukiki Barat, Parepare - Sitti Saleha Talib; Muhammad Siri Dangnga; Irmayani Irmayani (Sangia Publishing, 2020)
One of the agricultural commodities that is suitable to be developed with an agribusiness system is the commodity of decorative plants. This business plays an equally important role compared to other business sectors in the process of restoring growth and economic development in Indonesia. This is proven during the crisis, in which the decorative plant commodities as part of the horticulture sub-sector have played a role as a source of income with high added value for the farmers. This study aims to analyze the business strategy of decorative plant cultivation in the Pare-pare, to analyze external and internal factors. The research object is the Green House Garden and the Agriculture Office of Pare-pare. The data collection techniques used were interviews, questionnaires, observation and documentation involving 20 people as respondents. The data were analyzed by using qualitative descriptive analysis with a SWOT analysis approach. The results showed that the decorative plant business strategy in the Parepare was declared feasible because, based on the indicators of assessment aspect that have been determined, namely the ability of Green House Garden managers in achieving profitable sales volumes, the ability to produce better products compared to competitors, the ability to determine better prices compared to competitors, the ability to distribute better products and the ability to promote products more effectively than competitors, then the analysis of market and marketing aspects is considered feasible.